Calving photocensus of the Rivière George Caribou Herd and comparison with an independent census - Couturier, Serge; Courtois, Réhaume; Crépeau, Hélène; Rivest, Louis-Paul; Luttich, Stuart (Rangifer, 1996)
Vertical photographs of the calving grounds have been used since 1984 to estimate the caribou (Rangifer tarandus) population of the Rivière George Caribou Herd (RGCH) in Northern Québec and Labrador. In spite of large confidence intervals, the 1984 and 1988 estimates suggested that the herd stabilized at more than 650 000 caribou (fall estimate including calves) making the RGCH the largest caribou herd in the world. Between 1984 and 1990, studies suggested that the former rapid growth of the herd deteriorated the calving and summer habitats. This poor habitat quality affected physical condition, pregnancy rate and calf survival. It was important to have a valid estimate of the herd size and a photocensus was done in June 1993. Contrary to previous censuses, a slightly different sampling design was applied in 1993. Two methods were used to estimate the number of females in the June population. In the first method, the number of females was derived from the estimated number of calves on the photographs and from the June female/calf ratio. The second method was used in the previous census and is based on the number of adults on the photos and on the June female/adult ratio. It is suggested that the first method of estimating female abundance in June is better due to sampling problems associated with a strong adult sex segregation during calving. From the first method, the herd size in October 1993 was estimated at 583 829 adults (±33.79%) and at 749 869 caribou including calves (±33.15%) while the second method provided estimates of 764 221 adults (±23.55%) and 981 565 caribou including calves (±22.64%). It was possible to compare those population estimates with an independent census. In July 1993, an oblique photocensus of the post-calving aggregations was conducted by Russell et al. (1996). A new analysis of their raw data provided an estimate of 608 384 adults (±14.35%). Both estimates from the June and July photocensus were combined. From the first and second method respectively, combined herd size estimates ...